2000
DOI: 10.5194/aab-43-431-2000
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Milchfluss aus Eutervierteln

Abstract: Abstract. Title of the paper: Investigation of milk flow from udder quarters 672 milk flow curves of 30 cows from the milkings of one quarter and from the corresponding complete milkings of the respective following day were registered. With the aid of the ultrasound technique and an imaging analysis system the teat Channel lengths, the teat wall thickness and the teat tissue areas were meseared before and after milking. The duration of decreasing flow rate of the complete milking can be explained by the traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, the technical possibilities which provide the mobile measuring LactoCorder unit have implied the complete milk flow curve measuring as well as other parameters (GÖFT et al, 1994;NAUMANN et al, 1998;FAHR, 2002). The use of such modern measuring technical could result with a larger cow number adjusted to machine milking, and a small cow number with udder illnesses (ROTH et al, 1998;NAUMANN and FAHR, 2000;FAHR, 2002). The first research results performed by Lacto-Corder in Germany were used to define the value of certain milk flow curve parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the technical possibilities which provide the mobile measuring LactoCorder unit have implied the complete milk flow curve measuring as well as other parameters (GÖFT et al, 1994;NAUMANN et al, 1998;FAHR, 2002). The use of such modern measuring technical could result with a larger cow number adjusted to machine milking, and a small cow number with udder illnesses (ROTH et al, 1998;NAUMANN and FAHR, 2000;FAHR, 2002). The first research results performed by Lacto-Corder in Germany were used to define the value of certain milk flow curve parameters.…”
Section: Introductionmentioning
confidence: 99%
“…That means that by a longer dPFR and a shorter dDFR the udder was at least laden and less exposed to a possible infection. Such rate certainly leads to an even milking from all quarters and a "blind" milking prevention (NAUMANN et al, 1998;NAUMANN and FAHR, 2000;FAHR, 2002). The previous research showed that the somatic cell count in milk grows with the shortening of the milking time and increasing of the milk flow (MIJIĆ et al, 2003), what should be taken into consideration by selective animal choosing.…”
Section: Introductionmentioning
confidence: 99%